2012
DOI: 10.3989/mc.2012.01712
|View full text |Cite
|
Sign up to set email alerts
|

Desempeño a temperaturas altas de morteros y hormigones basados en mezclas de escoria/metacaolín activadas alcalinamente

Abstract: RESUMENEste artículo evalúa el desempeño de morteros y hormigones basados en mezclas de escoria siderúrgica (GBFS)/metacaolín (MK), activadas alcalinamente expuestos a temperaturas altas. Se identifica una elevada estabilidad en morteros con contenidos de MK de hasta un 60% cuando se exponen a temperaturas de 600 ºC, con una resistencia residual de 20 MPa posterior a la exposición a esta temperatura. Por otra parte, la exposición a temperaturas más elevadas conduce al agrietamiento de los hormigones como conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Prior studies have shown that the co-precipitation of these two gels in hybrid cements is possible (38)(39)(40)(41)(42)(43)(44)(45)(46), although recent research has revealed that the two products do not develop singly as two separate gels, but that they interact, undergoing structural and compositional change in the process (104).…”
Section: Co-precipitation Of Cementitious Gels: C-s-h + N-a-s-hmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that the co-precipitation of these two gels in hybrid cements is possible (38)(39)(40)(41)(42)(43)(44)(45)(46), although recent research has revealed that the two products do not develop singly as two separate gels, but that they interact, undergoing structural and compositional change in the process (104).…”
Section: Co-precipitation Of Cementitious Gels: C-s-h + N-a-s-hmentioning
confidence: 99%
“…Procedure 3: today, a mixed alkaline activation procedure, a combination of the preceding two, can also be described. The product in this case is a new type of binder known as a hybrid alkaline cement, formed as the result of the alkaline activation of materials with CaO, SiO 2 and Al 2 O 3 contents >20% (38)(39)(40)(41)(42)(43)(44)(45)(46).…”
Section: Alkali-activated Cementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that alkaliactivated materials derived from different sources can develop different properties based on the specific conditions of production, curing and testing. However, there is a good consensus that these materials can exhibit advantageous properties such as higher structural and dimensional stablity when exposed to high temperatures, when compared with Portland cement based materials (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reports that use SCMs, such as FA and MK, not only contributes to the reduction of environmental pollution, but also makes a positive contribution to the sustainability and durability of concrete and mortars [52][53][54]. Following from that, the purpose of this investigation was to examine the effects of partially replacing OPC with massive-generated materials from different production sources that would create a cementitious composite material with similar properties to the currently marketed binder, but without all of the detrimental effect to the environment.…”
Section: Discussionmentioning
confidence: 99%